Assessment of approach-avoidance tendencies in body image using a novel touchscreen paradigm. (March 2021) - Dondzilo, Laura; Basanovic, Julian; Bell, Jason; Mills, Caitlin; Dinic, Radomir; Blechert, Jens
Abstract: Background and objectives: Approaching the thin-ideal and avoiding the stigma of fatness are motivational tendencies resulting from the internalisation of sociocultural appearance norms. Individual differences in subclinical levels of eating disorder symptomatology may be related to variation in motivational tendencies regarding thin vs. non-thin bodies. Methods: To empirically investigate this hypothesis, the current study employed a novel touchscreen approach-avoidance task with the capacity to effectively simulate compatible approach-avoidance movements. Eighty-four undergraduate females pulled closer or pushed away images depicting either bodies or objects, in response to weight category (underweight bodies vs. overweight bodies) and object category (kitchen items vs. office tools), by means of arm movements. Results: Unexpectedly, results revealed relatively faster approach of overweight bodies and relatively faster avoidance of underweight bodies. Moreover, speeded approach towards overweight bodies, relative to underweight bodies, correlated positively with elevated eating disorder symptomatology. Limitations: The current sample was restricted to undergraduate women. Conclusions: The current study provides initial evidence for the utility of a touchscreen-based measure of approach-avoidance tendencies in body image, albeit comparison with other bias assessments would be necessary. Moreover, our findings suggest that a greater tendency to approach overweight bodies is associated with elevated eating disorder symptomatology. Future extensions of the current work are necessary to clarify the function of motivational tendencies in the body image context. Highlights: We assessed motivational tendencies with touchscreen-based arm movements. We found females tended to approach overweight bodies and avoid underweight bodies. Approach to overweight bodies was positively related to eating disorder symptoms.